An Effective Flat Plate Solar Heating and Cooling Hybrid System - M. Li; R.Z. Wang; F. Yun; F. Shi; L.L. Wang; H.L. Luo (Adsorption Science & Technology)
Based on the achievements of solar solid adsorption refrigeration research, a new hybrid heating and cooling system, related to the solar water heater technique, has been proposed. The conversion and utilization of solar energy for cooling and heating are also analyzed. Experiments on a prototype have shown that both the available (residual) and adsorption heats of the adsorbent bed can be recovered efficiently and simply. The results of some simulations of this new flat plate under real solar radiation are given, as well as comparisons with our previous research work. The successful design and assessment of this new flat plate hybrid system should accelerate the practical application of solid adsorption refrigeration driven by solar energy.